2018
DOI: 10.1177/1129729817747535
|View full text |Cite
|
Sign up to set email alerts
|

Randomized pilot study to compare metal needles versus plastic cannulae in the development of complications in hemodialysis access

Abstract: Background:Hemodialysis requires needle insertions every treatment. Needle injury (mechanical or hemodynamic) may cause complications (aneurysms/stenosis) that compromise dialysis delivery requiring interventions. Metal needles have a sharp slanted “V”-shaped cutting tip; plastic cannulae have a dull round tip and four side holes. Preliminary observations demonstrated a difference in intradialytic blood flow images and mean Doppler velocities at cannulation sites between the two devices. Complications from mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 44 publications
(59 reference statements)
4
28
0
Order By: Relevance
“…It is unlikely that the intimal hyperplasic reaction could travel from the anastomoses to the midportion of the graft. This finding would most likely validate the proposed theory by Roy-Chaydhury et al 3 Marticorena et al 4 studied the use of metal needles versus plastic cannulas. They found that plastic cannulas had a lower rate of infiltration.…”
Section: Discussionsupporting
confidence: 79%
“…It is unlikely that the intimal hyperplasic reaction could travel from the anastomoses to the midportion of the graft. This finding would most likely validate the proposed theory by Roy-Chaydhury et al 3 Marticorena et al 4 studied the use of metal needles versus plastic cannulas. They found that plastic cannulas had a lower rate of infiltration.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, training ensures the preparation of competent nurses so that as a professional group, nursing will gain the visibility and social recognition that it deserves. Therefore, it is worth highlighting again the low prevalence of training among Spanish HD nurses in PC, which are presented in the literature as a beneficial innovation for people with VAs requiring HD (Marticorena et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At this moment, we should also mention that the procedure for inserting PC differs considerably from that of conventional metal needles. This can lead to difficulties for the nurses, who require training and special skills to modify the needle insertion technique (Marticorena, Dacouris, & Donnelly, 2018). The existing data in the literature does not provide accurate indications about the type of device that should be used for each VA and, therefore, the choice is determined by the needs of each workplace, the availability of the device and on nurses' experience or training (Parisotto, Pelliccia, & Bedenbender‐Stoll, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dialysis plastic cannulae are an alternative to traditional metal needles and are used during hemodialysis procedures. The main advantage of plastic cannulae vs metal needles are the reduced risk of mechanical (internal vessel damages) and hemodynamic (shear stress) complications . However, the usefulness of this device was never reported in TPE.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of plastic cannulae vs metal needles are the reduced risk of mechanical (internal vessel damages) and hemodynamic (shear stress) complications. 3,4 However, the usefulness of this device was never reported in TPE.…”
Section: Introductionmentioning
confidence: 99%